Thermal Activation of Crystalline Silicon Ions in Alkaline Solution - Lamichhane, Shobha Kanta (Scientific World, 2010)
Anisotropic wet chemical etching of silicon in alkaline solutions (KOH) is one of the key techniques for the manufacture of microstructure. Fabrication of Micro-electro mechanical system (MEMS) part demand smooth surface finish and angular dependent etch rate. The absolute values of orientation dependent etch rate is found to vary with thermal agitation. In this work, experimental results of etch rate is found with their unusual values of activation energy along different planes. The various sites that an atom can occupy are not equivalent of their energy; some are more favorable to removal than others. In this paper attention is being given to demonstrate thermal activation is the prime factor that influences the behavior of etching mechanism as well as surface morphology. Atomic force microscopy (AFM) has been employed to analyze the morphology of the etched silicon surface at relevant elevated temperature. A systematic variation in morphological growth leads to stabilized surface structure under the influence of associated activation energy. Keywords: Activation energy; Etching; Anisotropy; Etch rate; MEMS; LPCVD; SOI. DOI: 10.3126/sw.v7i7.3817 Scientific World Vol.7(7) 2009 pp.15-18